2020
DOI: 10.3390/su12187516
|View full text |Cite
|
Sign up to set email alerts
|

LED Lighting Systems for Horticulture: Business Growth and Global Distribution

Abstract: In recent years, research on light emitting diodes (LEDs) has highlighted their great potential as a lighting system for plant growth, development and metabolism control. The suitability of LED devices for plant cultivation has turned the technology into a main component in controlled or closed plant-growing environments, experiencing an extremely fast development of horticulture LED metrics. In this context, the present study aims to provide an insight into the current global horticulture LED industry and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 43 publications
(86 reference statements)
0
25
0
Order By: Relevance
“…Lighting manufacturers are adopting the metrics used in the horticulture sector. However, a recent review [ 192 ] showed that 30% of the LED lighting system producers included in the study still do not report the photosynthetic photon efficacy of lamps.…”
Section: Led Lighting: Advantages and Challenges In Plant Growth Amentioning
confidence: 99%
“…Lighting manufacturers are adopting the metrics used in the horticulture sector. However, a recent review [ 192 ] showed that 30% of the LED lighting system producers included in the study still do not report the photosynthetic photon efficacy of lamps.…”
Section: Led Lighting: Advantages and Challenges In Plant Growth Amentioning
confidence: 99%
“…Besides, the benefits associated with hydroponics and possible de-humidification and water recovery from the internal atmosphere allow for elevated water use efficiency (Pennisi et al, 2020a), in the range of 30-50-folds the measured values in greenhouses and open-field cultivation (Kozai, 2013). On the other hand, the elevated energetic requirements (mainly due to electricity consumption associated with artificial lighting, Paucek et al, 2020) are still hindering the large-scale applicability of these systems (Kozai, 2019). Indeed, while technology is rapidly evolving, strategies for reducing the environmental burdens associated with PFALs are also being identified (Son et al, 2016;Pennisi et al, 2019cPennisi et al, , 2020cOrsini et al, 2020) and will likely foster the large-scale application of these technologies in the near future.…”
Section: Vertical Farms With Artificial Lightingmentioning
confidence: 99%
“…The low price of LEDs and the interest of the growers in investing in this technology has induced several companies to produce LED lighting systems for agriculture. The horticultural LED lighting market is promising and is expected to grow from USD 576 million in 2016 to USD 5.11 billion by 2022 [67]. In fact, in recent years, owners of high-latitude greenhouses have shown interest in replacing HPS lamps with more efficient LED modules, while owners of mid-latitude, e.g., Mediterranean, greenhouses are interested in installing SL.…”
Section: Light-emitting Diode Developmentmentioning
confidence: 99%
“…In fact, in recent years, owners of high-latitude greenhouses have shown interest in replacing HPS lamps with more efficient LED modules, while owners of mid-latitude, e.g., Mediterranean, greenhouses are interested in installing SL. Growers were encouraged by the positive effects of SL on horticulture crops obtained by researchers at Bari University [32,35,67,68]. High-latitude greenhouses tend only to replace their HPS lamps with LEDs, whereas new greenhouses or those installing artificial light for the first time have to design all the electrical components necessary for LED function (electrical cables, switch panels, hooks, software, etc.).…”
Section: Light-emitting Diode Developmentmentioning
confidence: 99%
See 1 more Smart Citation